Рефрактометрiя водних розчинiв етанолу поблизу особливої точки контракцiї - Bulavin, L. A.; Gotsulskiy, V. Ya.; Malomuzh, N. P.; Stiranets, M. V. (Publishing house "Academperiodika", 2019)
The concentration dependences of the refractive index in aqueous ethanol solutions at equilibrium have been studied experimentally. Special attention was paid to their behavior in a vicinity of the peculiar point defined as the intersection point of the concentration dependences of the contraction measured at different temperatures or as a point, at which the intensity of molecular light scattering has a maximum. The refractive index is found to noticeably deviate from its reference values in a vicinity of the peculiar point, 0.05 < x < 0.1 (x is the mole fraction of ethanol). This effect reflects the fact that the equilibrium properties of the solutions concerned are established only during a few weeks. Arguments that the system becomes microinhomogeneous in this concentration interval are presented.